A single untimed plasma drug concentration measurement during low-level HIV viremia predicts virologic failure. (December 2016) - Gonzalez-Serna, A.; Swenson, L.C.; Watson, B.; Zhang, W.; Nohpal, A.; Auyeung, K.; Montaner, J.S.; Harrigan, P.R.
Abstract: Suboptimal untimed plasma drug levels (UDL) have been associated with lower rates of virologic suppression and the emergence of drug resistance. Our aim was to evaluate whether UDL among patients with low-level viremia (LLV) while receiving highly active antiretroviral therapy (HAART) can predict subsequent virologic failure (plasma viral load ≥1000 copies/mL) and emergence of resistance. The first documented LLV episode of 328 consenting patients was analysed in terms of drug levels, viral load and resistance, which were monitored while patients were on a consistent HAART regimen. UDL of protease inhibitors (PIs) and non-nucleoside reverse transcriptase inhibitors (NNRTIs), were categorized as 'therapeutic' or 'subtherapeutic' based on predefined target trough concentrations. Drug resistance genotype was assessed using the Stanford algorithm. Time to virologic failure was evaluated by Kaplan–Meier analysis and Cox proportional hazards regression. We found 78 of 328 patients (24%) with subtherapeutic drug levels at time of first detectable LLV, while 19% harboured drug-resistant virus. Both subtherapeutic UDL and drug resistance independently increased the risk of subsequent virologic failure (p <0.001 and p 0.04, respectively). In a multivariable model, variables associated with LLV and virologic failure included subtherapeutic UDL, elevated plasma viral load, and drug resistance. Patients with subtherapeutic UDL accumulated further drug resistance faster during follow-up (p 0.03). Together, resistance and UDL variables can explain a higher proportion of virologic failure than either measure alone. Our results support further prospective evaluation of UDL in the management of low-level viremia.